Metabolically healthy and unhealthy obesity in erectile dysfunction and male infertility. Issue 5 (3rd September 2019) - Rastrelli, Giulia; Lotti, Francesco; Reisman, Yacov; Sforza, Alessandra; Maggi, Mario; Corona, Giovanni
ABSTRACT: Introduction : Metabolically unhealthy obesity (MUHO) is the most important preventable cardiovascular (CV) risk factor. Recently, the significance of metabolically healthy obesity (MHO) as a CV risk factor has raised increasing interest. MUHO is a known risk factor for erectile dysfunction (ED); however, the effect of MHO on ED has barely been investigated. This review aims at summarizing the evidence supporting the relation of MUHO and MHO to male sexual functioning and fertility. Areas covered : An extensive Medline search on obesity and ED or male infertility was conducted to summarize the role of MUHO or MHO on male sexual dysfunction and infertility. Expert opinion : Longitudinal studies have demonstrated that MHO causes vascular damage, which is consistent with the impairment in penile blood flows found in ED subjects. In this population, MHO is a predictor of CV events. The relationship between male infertility and MUHO is currently debated and data on MHO are almost completely lacking. The only available study did not find an association between obesity classes and semen parameters. Although the andrological correlates of MHO must be better assessed, in the current state, evidence suggests that MHO does not represent a benign condition and measures for improving lifestyle are mandatory.